Development of Interactive Multimedia Assisted with Powtoon Application on Global Climate Change Material to Facilitate Students' Knowledge and Technological Literacy Skills - Elpina, Selvi Tresa; Asrizal, Asrizal (Department of Physics Universitas Negeri Padang, 2025)
One of the most important skills in the era of industrial revolution 4.0 is technological literacy. This study aims to analyze the initial ability of knowledge aspects and technological literacy of students on global climate change material. The research method used was descriptive quantitative with a sample of 35 students of class X phase E at SMA N 2 Solok. Data processing was obtained from two categories, namely performance assessment instruments in the form of questions according to technological literacy indicators and teacher questionnaires. From the analysis of the performance assessment instrument, it was found that the indicator of knowing multimedia features in learning was 44% in the “low” achievement category. In addition, 45% of students are in the “low” achievement category on the aspect of knowing the various advantages of various technologies. A total of 41% of students are in the “low” achievement category on the aspect of using technology in learning. However, 43% of students were in the “low” achievement category in the aspect of selecting and utilizing technology in learning. The overall average in the category of achievement of students' technological literacy skills is 43% which is in the “low” category. The results of the teacher questionnaire on the aspect of using the learning model by the teacher, 56%, are in the “sometimes” category, the aspect of using printed teaching materials and learning media that are not based on it, 70%, are in the “often” category, and the aspect of using facilities and infrastructure, 43%, are in the “sometimes” category. Based on these results, it can trigger students' low technological literacy skills.